The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1055/s-0039-3402435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Examination and Various Imaging Modalities in the Diagnosis of Head and Neck Cancer

Abstract: Introduction Squamous cell Carcinoma of the Head and Neck (HNSCC) is the most common tumor entity of malignant processes in the head and neck area. Due to the metastasizing behavior of these tumors, the staging is indispensable for the treatment planning and requires imaging techniques, which are sensitive, specific, and as far as possible cost-effective, to benefit ultimately the patient and to ensure optimal care. Objectives The aim of the present study is to compare the clinical examination includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Due to the superficial localization, B-Mode ultrasound (US) is the primary imaging modality for detection and characterization by the use of high-frequency linear transducers [ 9 ]. Well known criteria for malignant lymph node transformation are round shape and loss of fatty hilus or cystic changes and Solbiati Index (ratio long-axis/short-axis) < 2 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the superficial localization, B-Mode ultrasound (US) is the primary imaging modality for detection and characterization by the use of high-frequency linear transducers [ 9 ]. Well known criteria for malignant lymph node transformation are round shape and loss of fatty hilus or cystic changes and Solbiati Index (ratio long-axis/short-axis) < 2 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many HNSCCs first present with signs and symptoms of CLN metastasis [2], where CLN involvement is a prognostic factor and influences the choice of treatment [3,4]. Close monitoring of CLNs is recommended in HNSCC patients [5], with ultrasound (US) being the image modality of choice [6]. In B-mode US, benign CLNs have an oval shape, a well-defined border and a hilus sign.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations from any of these morphological features are considered indicators of potential malignant involvement [7]. Even though the combination of B-mode US and CCDS shows a higher diagnostic performance than computer tomography or magnetic resonance imaging of the neck, its sensitivity of 66-91% and specificity of 61-78% are not yet satisfying [6,8]. Recent studies have demonstrated the added value of utilizing preoperative quantitative multiparametric US (mpUS) in inconclusive CLNs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%